(untitled) (European Bison Conservation Newsletter, 2009)
The study objective was to compare two methods used to determine serum levels of 17S-estradiol (E2) in European bison Bison bonasus (Linnaeus, 1758) males: the radioimmunological method (RIA) and the immunoenzymatic method (ELISA). The study material included sera from 101 European bison males aged 2 months – 19 years, which were culled in the autumn and winter periods (in the post-rutting season), in the years 1993–2002, in the Białowiez˙a Primeval Forest. E2 levels were determined using the two methods (RIA and ELISA) in the same animals. The following age groups were distinguished: class I – calves under the age of 1 year, class II –juveniles under the age of 2 years, class III –juveniles under the age of 3, class IV – adult males aged 4–5 years, class V – adult males aged 6–12 years, class VI-old bulls over the age of 12. Using the RIA method to determine serum concentrations of E2 in European bison males, all the values obtained were below the bottom limit for this method. However, the use of the ELISA method revealed serum levels of E2 in all the 101 males. The highest median serum levels of E2 were noted in the youngest European bison from age classes I and II, whereas the lowest in adult bulls (age class V), actively participating in reproduction. However, in the 4–5 -year-old animals (age class IV), sexually mature, but not involved in reproduction due to a lower status in the herd, the median serum level of E2 was nearly twice as high as in the class V bulls. The remaining European bison specimens (juveniles aged 3 years and old bulls over 12) had almost identical median serum levels of E2, the values falling in the middle, between the highest and the lowest median levels observed in the other animals. We found great individual differences in the serum levels of E2 in the respective animals in all the age classes studied.